(untitled) - Sarah Clark (New York, 1982)
The book has a three-part division with twelve chapters, ten of which are devoted to grammar ant the last two to paragraph writing. An appendix follows, containing useful information (such as rules for spelling and punctuation)
Keywords: english language - grammar - 1950-,englissh language - paragraphs